(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Project-Based Learning (PBL) has emerged as an effective approach in modern primary education, emphasizing student-centered learning through real-world tasks and collaboration. This article explores the implementation of PBL in primary classrooms, analyzes its educational benefits, and highlights the key challenges teachers and students face. Based on qualitative and quantitative data, the article suggests strategies to optimize PBL in early education.